Advances in laparoscopic surgery in urology - Rassweiler, Jens; Teber, Dogu (Nature reviews. Urology, 2016)
Laparoscopic techniques are subject to continuous change and benefit from new developments. Robot-assisted surgery has substantially revolutionized laparoscopy, increasing its distribution; however, it is associated with considerable costs. In this Review, Rassweiler and Teber discuss technical improvements, developing technologies and speculate on the future of minimally invasive surgery and laparoscopy in urology.
Gesehen am 11.03.2020